Transcriptome Profile of the Green Odorous Frog (Odorrana margaretae) - Qiao, Liang; Yang, Weizhao; Fu, Jinzhong; Song, Zhaobin (PLOS ONE, 2013)
Transcriptome profiles provide a practical and inexpensive alternative to explore genomic data in non-model organisms, particularly in amphibians where the genomes are very large and complex. The odorous frog Odorrana margaretae (Anura: Ranidae) is a dominant species in the mountain stream ecosystem of western China. Limited knowledge of its genetic background has hindered research on this species, despite its importance in the ecosystem and as biological resources. Here we report the transcriptome of O. margaretae in order to establish the foundation for genetic research. Using an Illumina sequencing platform, 62,321,166 raw reads were acquired. After a de novo assembly, 37,906 transcripts were obtained, and 18,933 transcripts were annotated to 14,628 genes. We functionally classified these transcripts by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). A total of 11,457 unique transcripts were assigned to 52 GO terms, and 1,438 transcripts were assigned to 128 KEGG pathways. Furthermore, we identified 27 potential antimicrobial peptides (AMPs), 50,351 single nucleotide polymorphism (SNP) sites, and 2,574 microsatellite DNA loci. The transcriptome profile of this species will shed more light on its genetic background and provide useful tools for future studies of this species, as well as other species in the genus Odorrana. It will also contribute to the accumulation of amphibian genomic data.